Detection of reduced carbon in a basalt analogue for martian nakhlite: a signpost to habitat on Mars. Issue 2 (April 2014) - Parnell, John; McMahon, Sean; Blamey, Nigel J.F.; Hutchinson, Ian B.; Harris, Liam V.; Ingley, Richard; Edwards, Howell G.M.; Lynch, Edward; Feely, Martin; Cockell, Charles; Burchell, Mark; Martins, Zita
Abstract The Nakhla meteorite represents basaltic rock from the martian upper crust, with reduced carbon indicative of the ingress of carbonaceous fluids. Study of a terrestrial analogue basalt with reduced carbon from the Ordovician of Northern Ireland shows that remote analysis could detect the carbon using Raman spectroscopy. Analysis of gases released by crushing detects methane-rich fluids in the basalt and especially in cross-cutting carbon-bearing veinlets. The results suggest that automated analysis on Mars could detect the reduced carbon, which may be derived from magmatic and/or meteoritic infall sources.